LEISHMAN GIEMSA COCKTAIL, A CYTOLOGICAL STAINING COMPARABLE TO PAPANICOLAOU STAIN FOR ORAL CANCER DIAGNOSIS – A PROSPECTIVE OBSERVATIONAL STUDY. - Mishra , Tapas Ranjan; Mishra, Pragnya Paramita; Dash, Monica; Panigrahi, Rakesh kumar (Student's Journal of Health Research Africa, 2025)
Background: Oral squamous cell carcinoma (OSCC) is the most common tumor in the head and neck region. Exfoliative cytology in the form of scrape cytology is a valuable aid for screening oral lesions. Aim: The study aims to evaluate and compare Pap, MGG, and LG cocktail staining in exfoliated cells of oral malignancy. Material & methods: This prospective study was conducted in the department of Pathology at Hitech Medical College, Rourkela, over a period of two years. According to conventional staining protocols, one air-dried smear was stained with MGG, and the other with LG cocktail, and the third with Papanicolaou stain. The stained slides were examined independently by two pathologists, and the results were recorded. Biopsy results were also compared with the cyst diagnosis. Statistical analysis was done. Result: The study evaluated the diagnostic efficacy of Pap, MGG, and LG cocktail stains in exfoliated cells of oral malignancy, specifically squamous cell carcinoma (SCC). Among the 103 suspected cases, 92 were diagnosed as SCC, with a 100% correlation between cyst diagnosis and histological results for SCC cases. The LG cocktail stain demonstrated the highest specificity at 95%, followed by Pap (93.7%) and MGG (93.2%). Sensitivity was similar across all stains, with LG cocktail slightly outperforming Pap and MGG. MGG showed the highest negative predictive value at 84.7%, indicating its superior ability to rule out malignancy. Conclusion: LG Cocktail staining is a simple, cost-effective, less time-consuming, one-step process and can be used for an oral cancer screening program. Most importantly, the LG cocktail staining technique was found to give results comparable to the Pap stain. Recommendation: It is recommended to use the LG cocktail stain for improved sensitivity and comparable specificity in diagnosing oral squamous cell carcinoma from exfoliated cells.